PENGGUNAAN LEVEL OF INQUIRY EMBEDED FORMATIVE ASSESSMENT (LoI-eFA) DALAM PEMBELAJARAN SISTEMATIKA HEWAN BERBANTUAN TAKSONOMI NUMERIK UNTUK MENGEMBANGKAN PENALARAN FORMAL-POSTFORMAL DAN KEMAMPUAN INKUIRI MAHASISWA - Aa Juhanda, - (2022)
This study aims to implement the use of integrated formative assessment level of inquiry (LoI-eFA) in developing formal-postformal operational reasoning and inquiry abilities of students in systematic learning of rock animals in numerical taxonomy. This study uses a mixed methods embedded experimental design. The participants in this study were 77 UMMI biology education students consisting of 29 general biology practicum students, 24 invertebrate zoology practicum students, and 24 vertebrate zoology practicum students. The research instrument used consisted of 28 questions of formal-postformal reasoning (divided into groups A and B), a rubric for assessing inquiry abilities, student response questionnaires, and lecturer interview formats. The results showed that the use of the LoI integrated assessment in developing formal-postformal operational reasoning for prospective teachers showed an increase in the average pretest and posttest results obtained by students in general biology, invertebrate zoology, and vertebrate zoology practicums. The results of the one way ANOVA statistical test obtained a significance value of 0.001 <0.05, so it can be concluded that the average value of the formal-postformal reasoning of the three participants was significantly different. In general biology practicum students, the highest indicator of formal-postformal reasoning was achieved by control variables and the lowest was in metasystematic reasoning. In invertebrate zoology practicum students, the highest indicator of formal-postformal reasoning is achieved by proportional reasoning and the lowest is metasystematic reasoning. In vertebrate zoology practicum students, the highest indicator of formal-postformal reasoning is achieved by proportional reasoning and the lowest is systematic reasoning. Students' inquiry skills developed through the use of LoI-eFA showed an increase in each meeting. Students and lecturers gave positive responses to the implementation of the use of LoI-eFA in developing post-formal reasoning and inquiry skills.